TECTONO-SEDIMENTARY STRUCTURE AND LATE QUATERNARY EVOLUTION OF THE NORTH EVIA GULF BASIN, CENTRAL GREECE: PRELIMINARY RESULTS - Sakellariou, D.; Rousakis, G.; Kaberi, H.; Kapsimalis, V.; Georgiou, P.; Kanellopoulos, Th.; Lykousis, V. (Bulletin of the Geological Society of Greece, 2007)
Systematic single channel seismic and 3.5 kHz profiling, gravity and box coring and Pb downcore analyses shed light to the structure and the Late Quaternary evolution of the North Evia Gulf graben. The latter is segmented along its axis in three distinct basins. The shallow, E-W striking western basin displays southward asymmetry. The NW-SE striking, deep central basin and the shallow southeastern one show NE-ward asymmetry and are controlled by the Aidipsos, Telethrion and Kandili fault zones. Sequence stratigraphie data and aragonite crystals in mud layers underlying Holocene deposits verifies that North Evia Gulf was a lake during the last glacial maximum with lake level at about 90m below the present sea level.